Quantum Sensing Experiments with Superconducting Qubits - Schneider, Andre (Experimental Condensed Matter Physics, 2021)
Quantum sensing is a vast and emerging field enabling in-situ studies of quantum systems and hence the development of quantum hybrid systems. This work creates the fundament of direct superconducting-magnetic hybrid systems by developing a local microwave sensing scheme and studying the influence of a static magnetic field on a superconducting qubit. Finally, a proof-of-principle hybrid system is demonstrated, which opens the path towards superconducting-magnetic quantum circuits.